(untitled) (Zaporizhzhia Historical Review, 2021)
This article present the ideas of N. D. Polonska-Vasilenko on the starshina of Zaporozhye in the 18th century. The author analyzes Polonska-Vasilenkoís achievements in the context of historiographic situation of 1920-1930th and defines the contribution of this scholar to the research of the starshina of Zaporozhye of the 18th century as the separate social group.